2020
DOI: 10.1038/s41598-020-65264-x
|View full text |Cite
|
Sign up to set email alerts
|

Automated detection of the head-twitch response using wavelet scalograms and a deep convolutional neural network

Abstract: Hallucinogens induce the head-twitch response (HTR), a rapid reciprocal head movement, in mice. Although head twitches are usually identified by direct observation, they can also be assessed using a head-mounted magnet and a magnetometer. procedures have been developed to automate the analysis of magnetometer recordings by detecting events that match the frequency, duration, and amplitude of the HTR. However, there is considerable variability in the features of head twitches, and behaviors such as jumping have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 52 publications
1
29
0
Order By: Relevance
“…Finally, these processes yield the statistics of behavioral analysis in multiple cages where animals freely behave ( Fig. 2 B (4) and (5) ). SI Appendix , Movie S1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, these processes yield the statistics of behavioral analysis in multiple cages where animals freely behave ( Fig. 2 B (4) and (5) ). SI Appendix , Movie S1.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, the absence of highthroughput pipelines for the analysis of behavior in untethered, freely moving animals has limited progress. Recently, deep convolutional neural networks (DCNNs) have been developed that enable computer vision-based quantitative analysis of behavior (5,6). These methods involve Mask R-CNN, DeepLab, and DeepLabCut (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…The approach in [18] uses a similar encoding but for multiple time series. Other approaches have proposed to use a Short-time Fourier Transform (STFT) or Wavelet transform spectrogram to represent the time-series into image form (e.g., [19][20][21][22]).…”
Section: Image Representations Of Time Seriesmentioning
confidence: 99%
“…We decided for a set of patterns that are simple to compute and that can help effectively distinguish between different activities. Other methods in the literature have considered to either depict directly part of the signal on the image or depict the result of signal transformations such as Fourier Transform (e.g., [19]) or Wavelet Transform (e.g., [20][21][22]). In the first case, the design effort is placed on the neural network architecture, which is something we are seeking to avoid with our approach.…”
Section: Patterns Over Timementioning
confidence: 99%
“…The scalogram of the whole set of coefficients, represented as an image, has been used for decoding using various types of deep learning neural network decoders. 54,55 Here, we only selected a set of prominent coefficients as a feature set for decoding, and showed that a small set selected by WCMI is able to decode a significant portion of information. This feature extraction step can capture essential information embedded in the whole set of coefficients.…”
Section: Advantages and Limitationsmentioning
confidence: 99%